Media Exposure, Gender Diversity, and Managerial Ownership of CSR Disclosure: The Moderation Effect of the Independent Board of Commissioners - Amalia Indah Fitriana; Dede Sunaryo; Januar Eky Pambudi; Mikrad; Siti Nurhaliza; Hendra Galuh Febrianto (www.amertainstitute.com, 2025)
This study examines the influence of media exposure, gender diversity, and managerial ownership on corporate social responsibility (CSR) disclosure, with independent board of commissioners as a moderating variable. Conducted on Consumer Non-Cyclicals sector companies listed on the Indonesia Stock Exchange from 2018-2022, this research addresses the growing importance of CSR transparency in building stakeholder trust and corporate accountability. Using purposive sampling, eleven companies were selected as samples, with secondary data analyzed through panel data regression and moderation regression. Findings reveal that gender diversity and managerial ownership significantly influence CSR disclosure, while media exposure shows no significant effect. The independent board of commissioners effectively moderates the relationship between gender diversity and managerial ownership with CSR disclosure, but fails to moderate media exposure's impact. This research contributes to corporate governance literature by identifying the supervisory role of independent commissioners in strengthening the relationship between firm characteristics and CSR disclosure. The findings provide practical implications for management in enhancing social transparency and offer regulatory insights for developing more effective corporate governance policies, particularly within the Indonesian business context.